Bone Mineral Density in Patients With Coxarthrosis With Concomitant Spinal Pathology - Haluzynskyi, O.A.; Haiko, O.G.; Gayko , G.V. (TERRA ORTHOPAEDICA, 2020)
Summary. Relevance. Combined pathology of the lumbar spine and hip joint is rightly considered one of the serious problems of modern orthopedics. Among the many factors that can cause lumbar spine pain, a decrease in bone mineral density (BMD) of the vertebral bodies in the form of osteoporosis may play a role. Objective: to study BMD in patients with osteoarthritis of the hip joints with concomitant pathology of the spine. Materials and Methods. The analysis of data of densitometric and statistical research of 62 patients who had grade III-IV coxarthrosis (CA) with concomitant pathology of the spine was carried out. Results. Decreased BMD in patients with grade III CA was found in 22 (35.4%) in the form of osteopenia and in 8 (12.9%) as osteoporosis; in patients with grade IV CA – in 4 (6.4%) and in 17 (27.4%) – respectively. It was found that BMD in patients with grade IV CA is significantly lower than in patients with grade III and there is a probable medium-strength relationship between a stage of CA and BMD of the femoral neck. It has been proven that patients with hypoplastic coxarthrosis and the true form of lumbar vertebral syndrome (LVS) have probably lower mean BMD values and exactly these groups of patients have the highest incidence of osteopenia and osteoporosis. Conclusions. 51 (82%) patients with grade III-IV CA revealed a decrease in BMD in the form of osteopenia and osteoporosis, the degree of which depends on the severity of the disease and functional insufficiency of the limb. Changes in BMD have their own characteristics in patients with different types of CA and forms of LVS.